Freedom and Praxis in Plotinus’s Ennead 6.8.1-6 - Andrade, Bernardo Portilho (Revista Archai, 2020)
In this paper, I argue that Plotinus does not limit the sphere of free human agency simply to intellectual contemplation, but rather extends it all the way to human praxis. Plotinus’s goal in the first six chapters of Ennead 6.8 is, accordingly, to demarcate the space of freedom within human practical actions. He ultimately concludes that our external actions are free whenever they actualize, in unhindered fashion, the moral principles derived from intellectual contemplation. This raises the question of how the freedom of practical actions might relate to the freedom of intellectual contemplation. After considering two previously offered models ”“ a model of double activity, and an Aristotelian model of practical syllogism ”“ I offer a third alternative, namely a model of moral attunement, according to which our rational desires assume a kind of ‘care of the soul’ through active supervision. Practical life is thus imbued with freedom to the extent that the soul supervises its actions to conform to its will and choice of the good.